Influencing Factors of Cross-Border E-Commerce in China's Exports to Asean - Qiqi, Qiqi; Purwanto, Purwanto (DPPM Universitas Pelita Bangsa, 2023)
The research aims to analyze the impact of GDP, per capita income, total population, internet coverage, transportation costs, and economic freedom index on the size of cross-border e-commerce exports. This study uses quantitative research by obtaining data from the World Bank and Customs system and analyzing it using EViews12. There are six independent variables and one dependent variable. The technique used for the panel data multiple linear regression is the fixed effects model. In this paper, based on the data related to China's cross-border e-commerce exports to the ten ASEAN countries from 2013 to 2022, GDP, total population, per capita income, and transportation cost, Internet coverage and economic freedom index are selected as the six independent variables. The dependent variable is the scale of China's cross-border e-commerce exports to each country. The technique used for panel data multiple linear regression is fixed effect model, The technique used for panel data multiple linear regression is fixed effect model. It is concluded that GDP, total population, Internet coverage, and transportation cost have a significant impact on China's cross-border e-commerce exports to Indonesia, showing a strong significance.